Effect of prior clopidogrel use on outcomes in medically managed acute coronary syndrome patients. Issue 15 (30th March 2016) - Chin, Chee Tang; Boden, William E; Roe, Matthew T; Neely, Benjamin; Neely, Megan L; Leiva-Pons, Jose L; Corbalán, Ramón; Gottlieb, Shmuel; Dalby, Anthony J; Armstrong, Paul W; Prabhakaran, Dorairaj; Fox, Keith A A; et al.
Abstract : Objective: We investigated whether prior clopidogrel influenced long-term ischaemic and bleeding risks and modified the randomised treatment effect of clopidogrel versus prasugrel among medically managed patients with acute coronary syndromes (ACS) treated with dual antiplatelet therapy. Methods: Medically managed patients with ACS in the Targeted Platelet Inhibition to Clarify the Optimal Strategy to Medically Manage Acute Coronary Syndromes (TRILOGY ACS) trial were randomised to clopidogrel versus prasugrel (plus aspirin), stratified by prior clopidogrel use. From the analysis population (n=8927), we compared two groups: 'clopidogrel in-hospital (n=6513)' (clopidogrel started ≤72 h of presentation for index ACS event) and 'prior-clopidogrel (n=2414)' (on clopidogrel ≥5 days before index hospitalisation). Treatment-related differences in ischaemic (all-cause death, cardiovascular (CV) death, myocardial infarction (MI), stroke and the composite of CV death/MI/stroke) and bleeding outcomes (severe/life-threatening or moderate bleeding events based on Global Use of Strategies to Open Occluded Coronary Arteries (GUSTO) criteria) through 30 months were analysed between patients in the two groups. Results: Compared with 'clopidogrel in-hospital, ' 'prior clopidogrel' patients were younger (median 64 years vs 66 years, p<0.001), more likely to have prior CV events/revascularisation, and had a higher frequency of CV death, MI or stroke through 30 months (20.8% vs 18.2%, p=0.002), with no difference in bleeding events (2.3% vs 3.4%, p=0.50). Randomised treatment effect (prasugrel vs clopidogrel) was similar for ischaemic and bleeding outcomes in both groups (all pinteraction >0.05). Conclusions: Patients receiving clopidogrel before admission for ACS and subsequently treated only medically are at higher risk for CV events versus those not previously receiving clopidogrel. More potent antiplatelet inhibition with prasugrel versus clopidogrel did not significantly reduce this risk. Trial registration number: NCT00699998.